2013
DOI: 10.1016/j.bbi.2013.07.010
|View full text |Cite|
|
Sign up to set email alerts
|

Bone marrow mononuclear cells exert long-term neuroprotection in a rat model of ischemic stroke by promoting arteriogenesis and angiogenesis

Abstract: Transplanted bone marrow-derived mononuclear cells (BMMNCs) can promote arteriogenesis and angiogenesis by incorporating into vascular walls and differentiating into smooth muscle cells (SMCs) and endothelial cells (ECs). Here, we explored whether BMMNCs can enhance arteriogenesis and angiogenesis and promote long-term functional recovery in a rat model of permanent middle cerebral artery occlusion (pMCAO). Sprague-Dawley rats were injected with vehicle or 1×107 BMMNCs labeled with BrdU via femoral vein 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Bone marrow and peripheral blood mononuclear cells were collected as previously described (Wang et al, 2013). The mice were sacrificed after a sublethal intraperitoneal injection of 4% chloral hydrate.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow and peripheral blood mononuclear cells were collected as previously described (Wang et al, 2013). The mice were sacrificed after a sublethal intraperitoneal injection of 4% chloral hydrate.…”
Section: Methodsmentioning
confidence: 99%
“…However, the underlying mechanism of action for intravenous transplantation of BMMNCs in ischemic diseases is unclear. Some investigators have shown that transplanted cells, such as MSCs [39], neural stem cells [40], endothelial progenitor cells [41], and BMMNCs [7, 19, 28], are able to migrate to the ischemic lesion, remain viable, and function effectively via paracrine effects or cell differentiation. However, others have reported that, after intravenous delivery, most BMMNCs are initially trapped in the lungs or liver [14, 42].…”
Section: Discussionmentioning
confidence: 99%
“…BBB leakage, however, may also make it easier for BMMNCs to enter the ischemic brain. Previous studies have shown that BMMNCs could not penetrate the healthy rat brain, but were able to migrate into the infarct area after MCAO [7, 9]. We hypothesized that supplying exogenous VEGF would facilitate the migration of BMMNCs into the chronically ischemic brain of 2VO rats, thus enhancing their therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 Cellbased therapies, either transplantation of exogenous cells or stimulation of endogenous cells, are considered a promising means of treating stroke. [2][3][4][5][6] Approaches using bone marrowderived cells (BMCs) are particularly attractive because BMCs can be easily obtained and permit autologous transplantation. 7 Besides transplantation of exogenous cells, endogenous BMCs can be mobilized by the granulocyte colony-stimulating factor (G-CSF).…”
mentioning
confidence: 99%